High rise building deformation monitoring with GPS - Wan Akib, Wan Abdul Aziz; Shu, Kian Ko; Mat Amin, Zulkarnain (2004)
The timely identification of deformation associated with geologic hazards or ground settlement can save lives, avert large financial liabilities and avoid severe environmental damage. Nowadays, it is tempting to consider whether the GPS technology has an important role to play for monitoring the tall buildings still under normal behavior. The advantage of using GPS technology is that it can detect if the structure has drifted until a few centimeters. Besides that, GPS provides cost effective and 3D information that will useful for engineering geologists. A discussion is presents the study on the suitability of using GPS technology for detecting the displacement of the tall buildings and GPS based methods for the monitoring and modeling of the dynamic structures likes high-rise buildings.